Faith Across Geographies: Comparative Study of Ahmed Deedat and Maulana Abul Hasan Ali Nadwi’s Interfaith Dialogue - Umme Ammara (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2024)
This paper is based on a comparative analysis of the approaches of renowned Islamic scholars Ahmed Deedat and Maulana Abul Hasan Ali Nadwi, explicitly focusing on their contributions to interfaith dialogue, who influenced people worldwide with their vision and prophetic voice. Ahmed Deedat moved to South Africa in the 1930s and was known for his assertive and confrontational style. He gained international recognition for his debates with proponents of various faiths. His emphasis on comparative religion and direct engagement with opposing viewpoints sparked widespread interest and discussions within the global religious landscape. And influenced most Christians, while Maulana Abul Hasan influenced people in India, co-founded the World Islamic Mission, and adopted a more conciliatory and scholarly approach to interfaith dialogue. His emphasis on academic discourse, mutual respect, and finding common ground aimed to foster a harmonious coexistence among religious communities. At its core, this paper reexamines their personal and professional growth in their journey of becoming Islamic scholars and their influence on both Muslims and Non-Muslims in their respective countries. However, I will compare and contrast their approaches to chart out the basic needs and methods they used to move a larger mass to follow Islam amid major socio-political crises in their respective places.